Insulinoma in pediatric tuberous sclerosis complex: a case report - Librandi, Katia; Grimaldi, Serena; Catalano, Silvia; Moro, Francesco; Vallero, Stefano Gabriele; Spada, Marco; Porta, Francesco (Frontiers in Pediatrics, 2023)
Background Tuberous sclerosis complex (TSC) is a rare multisystemic disorder. This genetically determined disease is characterized by highly variable clinical expression, including epilepsy as a common feature. Seizures can also occur as a manifestation of symptomatic hypoglycemia. The latter could be caused by an insulinoma, whose association to TSC has already been debated. In TSCassociated tumors, dysregulation of the mTOR pathway is believed to be present, leading to significant impacts on cellular metabolism, growht, and proliferation. To date, the association between TSC and insulinoma has been reported in 11 adults. Here, we present the first case of a pediatric patient with TSC diagnosed with an insulinoma and review the existing literature on this topic.Case presentation A 11-year-old female with TSC presented with seizures unresponsive to standard therapy. Further investigation revealed that these seizures were caused by hypoglycemia. Subsequent evaluation led to the diagnosis of a pancreatic insulinoma, which was surgically removed. Following the procedure, the patient was free from seizures.In individuals with TSC, the recurrence of epileptiform episodes throughout their lifetime, especially if previously well controlled with antiepileptic therapy, should raise suspicion for hypoglycemic events. These events may potentially be associated with the presence of an insulinoma.Further research and increased awareness are necessary to gain a better understanding of the association between TSC and insulinomas, and to guide clinical management strategies.